Incubation of companies based on knowledge: innovation and university- company linkage in UNAM - Patiño Cabrera, Alejandra; González Rabadán, Erika Leticia; Martínez Rivera, Sergio Efrén (mktDESCUBRE; Vol 1 No 12 (2018): Twelfth Edition - (July - December), 2018)
In the present work the advances of the National Autonomous University of Mexico (UNAM) are shown in terms of university-business linkage, with the awareness that In the knowledge society, universities acquire an increasingly active role in the transformation of societies where research, innovation and technology transfer, play a fundamental role and become strategic actors of national development through incubation and creation of companies; Thus, universities must focus on overcoming the challenges that lead them to consolidate their links with companies and organizations in the productive, governmental and social sectors, thus strengthening a triple helix model. This paradigm represents for public universities, by its nature, the double challenge of contributing through the strengthening of the business sector mainly in the industrial and technological fields, and the opportunity to contribute to a less unequal society through economic development based on the creation and use of knowledge.